2014
DOI: 10.1016/j.ieri.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Computing and Application Particularities of no Restoring Mechanism Aseismic Control Device

Abstract: In this research presented modelling, computing and application particularities of the structural aseismic control device which response redaction effect an average 61-79% relatively to conventional structure under earthquake excitation. For modelling mention device reinforce solid, structural solid, spring and contact finite elements was used. For contact element accepted conventional Coulomb frictional model. Governing non linier equation of motion is modelled as multidegree of freedom system with discontinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…So that the physical model of the structure is shown in Figure 2. To see in more detail the beam element is approached with standard equilibrium and kinematics [31]. With that approach, the beam element can be described in Figure 3.…”
Section: Figure 1 Physical Model In a Spring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…So that the physical model of the structure is shown in Figure 2. To see in more detail the beam element is approached with standard equilibrium and kinematics [31]. With that approach, the beam element can be described in Figure 3.…”
Section: Figure 1 Physical Model In a Spring Systemmentioning
confidence: 99%
“…With that approach, the beam element can be described in Figure 3. By using the basic concept of Euler-Bernoulli theory [31], where…”
Section: Figure 1 Physical Model In a Spring Systemmentioning
confidence: 99%
“…A single-degree-of-freedom system is described as a spring-mass-damper system. However, to see the response of the building structure more accurately, a multi-freedom system is used [12]. This study uses the concept of a freedom system because the floor of the building to be studied is more than one floor.…”
Section: Structural Dynamicsmentioning
confidence: 99%
“…A number of researches have been conducted on this type of sliding material and its characteristics were experimentally studied [2][3][4]. The Natural Seismic Isolation (NSI) with Horasan mortar as the interface material was devised when the "Walled Obelisk" monument was modeled for investigation in terms of its structural safety [1,[5][6][7][8][9][10][11]. The results of the research showed that the bottom part of the monument acts as a Published on February 27, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The responses were in the range of 50-80% reduction. The responses of interest for PF systems including friction coefficient, peak sliding velocity and displacement, are shown for various other researchers [5][6][7][8][9][10][11][20][21][22][23][24]. In this study, authors aim to demonstrate the possibility to use Horasan mortar as a…”
Section: Introductionmentioning
confidence: 99%